Awareness and practice of safety precautions among healthcare workers in the laboratories of two public health facilities in Nigeria (2011)
Aims and objectives: To determine the level of awareness and practice of SP among laboratory workers at two tertiary public health facilities in Nigeria. Methods: A semi-structured, self-administered questionnaire was used to assess the awareness, attitude and adherence to SP among laboratory workers. Information on the availability of safety equipment was also sought. The laboratory safety practice of respondents was assessed based on self-reported observance of basic principles of universal precautions in clinical settings. Results: Study participants were 130, mean age: 28.2 years (SD±6.6), number of years in hospital employment: 3.7 years (SD±2.4) and the male to female ratio was 1.8:1. Many (41.5%) were unaware and 25.4% do not observe SP. Participants attest to availability of various safety devices and equipment including hand gloves (86.2%), disinfectants (84.6%), HBV immunization (46.2%) and post exposure prophylaxis (PEP) for HIV and HBV (79.6%).Attitude to safety is unsatisfactory as 60.0% eat and drink in the laboratory, 50.8% recap needles and 56.9% use sharps box. Even though 83.1% are willing to take PEP, only 1.5% will present self following laboratory injury. Conclusion: This study shows the deficit in the awareness of SP among laboratory personnel and demonstrates that attitude and practice of safety rules are unsatisfactory. Training and re-training on SP is therefore desired. Counselling to induce a positive attitudinal change on HBV immunisation and PEP is similarly necessary.